Iklan dan Budaya Popular: Pembentukan Identitas Ideologis Kecantikan Perempuan oleh Iklan di Televisi - Fitryarini, Inda (Jurnal ILMU KOMUNIKASI, 2009)
Abstract: Mass media is not only a channel to deliver messages but also is a channel to build a special image about the world, such as the beauty image of women. Advertisements create it in their messages. Most of them show women with white skin, slim and have long black hair. These cases are a part of popular culture or mass culture because it could be a homogen-standard value. Advertising is related with popular culture. Advertising is a reflection of popular culture and it is an inventor of popular culture.